Data on assessment of flours from advanced genotypes and improved cassava varieties for industrial applications - Chimphepo, L.; Alamu, Emmanuel Oladeji; Monjerezi, M.; Ntawuruhunga, P.; Saka, J.D.K. (Elsevier, 2021)
The data presented in this article are related to the research paper “Physicochemical parameters and functional properties of flours from advanced genotypes and improved cassava varieties for industrial applications” [1]. The genotypes were collected from a multi-location (Uniform yield Trial) trial of the IITA breeding program in Malawi. The data were obtained using multiple analytical techniques and methodology such as oven-drying, sieving, colorimetry, titration, acid hydrolysis method, the Kjeldahl procedure, UV/VIS spectrophotometry, and centrifugation.The data set contains physicochemical parameters described dry matter (on fresh weight basis), moisture content, pH and total titratable acidy, the content of ash, bulk density; chemical properties were described by total cyanogen potential, total starch, amylose, amylopectin, crude protein and total carbohydrates; functional properties were described by swelling power, water solubility, water binding capacity and oil absorption capacity. The presented data are valuable for cassava breeders, food scientists, nutritionists, and other researchers working on breeding and processing cassava for innovative product development from cassava flour.